Analisis Fatwa Mui Sumatera Utara Tentang Penjualan Kulit Hewan Kurban Di Kelurahan Pekan Tanjung Pura - Ade Irza Zuliansyah; Ahmad Sanusi Luqman2 (Journal Smart Law, 2023)
Sacrifices are offered as a form of taqarrub to Allah, that is, to get closer to Him. Sacrifice is an animal that is slaughtered on Eid al-Adha and tasyriq days. At the time of slaughter, the ownership of the victim is lost. Therefore, it is forbidden to sell qurbani skins, as the MUI of North Sumatra has decreed. As happened in Pekan Tanjung Pura sub-district, in several prayer rooms the committee did not distribute sacrificial skins. The reason is because in that area it is difficult for the recipients of the sacrificial meat to process the sacrificial skin. Therefore, they sell the sacrificial skins to gravel workers or ox skin traders, and the proceeds from the sale are used by the committee or put into the mushalla treasury. From these problems, it is necessary to conduct research related to the sale of sacrificial animal skins in the Pekan Tanjung Pura Village, and an analysis of the North Sumatra MUI Fatwa on this sale. This study aims to determine the practice of selling sacrificial animal skins in the Pekan Tanjung Pura Village, as well as knowing the contents and analysis of the NS MUI fatwa regarding the sale of sacrificial animal skins. The type of research used is field research with a qualitative approach. The data were collected using interview and observation techniques, with primary data coming from interviews with the qurban committee and NS MUI fatwa, supported by secondary data coming from books and fiqh books. Furthermore, the data is then organized, synthesized, arranged into patterns, and concluded. The results of the research are: first, NS MUI in its fatwa forbids the sale of sacrificial animal skins; second, the committee considers the sale of sacrificial animal skins to be khilafiyah and may be sold; third, the sale of sacrificial animal skins at Tanjung Pura Week is illegal based on the NS MUI Fatwa.